Relationship of Anemia in Pregnancy with Postpartum Hemorrhage in Jombang Regional Hospital - Farah Luthfia Nugroho; Ninuk Dwi Ariningtyas; Yudith Annisa Ayu Rezkita; Pribakti Budinurdjaja; Muhammad Anas (Indonesian Journal of Medical Sciences and Public Health, 2020)
Introduction: Based on the Health Profile of East Java Province it was noted that the maternal mortality rate is still high, with the highest cause of maternal death being preeclampsia/eclampsia which is 28.92%, and hemorrhage by 26.28%. Mothers with anemia have a higher risk of postpartum hemorrhage. This is caused by the lack of oxygen and nutrients in the uterine organs, resulting in a decrease in myometrium muscle contraction that causes hemorrhage. Objective: To determine the relationship between anemia in pregnancy and postpartum hemorrhage in Jombang Regional Hospital 2016-2019. Method: Researchers use analytic research with a case-control approach. The study population of women who experienced hemorrhage at Jombang Regional Hospital in 2016-2019 (as a case group population). And women who did not experience hemorrhage at Jombang Regional Hospital in 2016-2019 (as a control group population). The sample of each study was 36 respondents for the case and control groups with a non-probability sampling technique consecutive sampling, and a matching process was carried out. Results: The significance value in the Mann Whitney test was 0.000 (p<0.05), which means that H0 was rejected, there was a significant relationship between anemia in pregnancy and postpartum hemorrhage in Jombang Regional Hospital. As well as the strength of the relationship between anemia and postpartum hemorrhage which was calculated using the Contingency Coefficient test. shows a figure of 0.582, which shows a positive correlation with sufficient strength correlation. Conclusion: Based on the results of research that has been done shows that there is a relationship between anemia in pregnancy with postpartum hemorrhage in Jombang Regional Hospital 2016-2019.